Typology of risks of territories of advanced development - M. A. Arzumanyan; O. I. Larina; N. V. Moryzhenkova (Управление)
The article deals with the one of the most difficult aspects of the implementation of public-private partnership (PPP) - risk management. That partnership is the answer to the solution of problems with the choice of an effective way of development of transport, social, communal and other infrastructure. The practice of using PPP forms is gaining popularity in the territory of Russia. The authors considers the matters of the Russian economy improvement by readjustment the existing risk management paradigm of a PPP. An integral part of highly professional risk management is the definition of management objects in the economic sphere. A number of controversial issues related to classifications of risks of PPP is raised in the article. Since the domestic theory has not yet solved the problem of clear and comprehensive risk identification in the implementation of projects based on PPP, it is necessary to develop such a classification is now becoming particularly relevant. Various available points of view on this issue are analyzed. The authors propose their position on the classification of risks for the territories of advanced development proceeding from the environment of their origin. The developed classification will help stimulate the PPP market from a practical point of view in different sectors. The modern advantages of using advanced development territories in the Russian Federation and recommended them as an organizational model of PPP are revealed. It should be noted that to date there is no single system of documents for the development of regional infrastructure, which causes a lot of uncertainties in the course of making a decision on this transaction.